2021
DOI: 10.1177/17085381211007612
|View full text |Cite
|
Sign up to set email alerts
|

Popliteal entrapment syndrome—The case for a new classification

Abstract: Objectives To assess the ability of the current classification system for popliteal entrapment syndrome to accurately capture all patients, and if not, to design an all-inclusive new classification. Methods Retrospective review of all interventions performed for popliteal entrapment syndrome between 1994 and 2013 at our institution was performed. Preoperative imaging and intraoperative findings were used to establish the compressive morphology of popliteal entrapment syndrome. Patients were categorized, when p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Based on the early classification of popliteal entrapment syndrome described by Rich et al, 7 the etiology of our patient does not conform to any type. However, in the new classification system proposed by Jayaraj et al, 8 the etiology of our patient is classified as type III, vein (V), lateral (L). According to the study by Koplas et al, 9 the anomaly of the GCM observed in the present case is not uncommon, present in 1.9% of patients who underwent knee magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 89%
“…Based on the early classification of popliteal entrapment syndrome described by Rich et al, 7 the etiology of our patient does not conform to any type. However, in the new classification system proposed by Jayaraj et al, 8 the etiology of our patient is classified as type III, vein (V), lateral (L). According to the study by Koplas et al, 9 the anomaly of the GCM observed in the present case is not uncommon, present in 1.9% of patients who underwent knee magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 89%